Teacher's Experience towards Online Learning Pre Covid-19 Pandemic in Aceh - Rina Mirdayanti; Jamratul Ula; Linda Junia Ningsih; Lindawati, Lindawati; Sari Wardani (JTP - Jurnal Teknologi Pendidikan, 2022)
The Covid-19 pandemic has affected almost every aspect of life in the world, including education. The learning process, which was originally done face-to-face at school is diverted to the home using the online learning model. The inequality of the teacher's ability to utilize technology affects the achievement of this online learning goal. The ability of teachers to conduct online learning depends on knowledge and experience in online teaching before the Covid-19 pandemic. Objective: This study was conducted to expose information related to teachers’ experience toward online learning before the Covid-19 pandemic. Method: The study was carried out by implementing a descriptive quantitative method. The instrument used in this study was questionnaires distributed online using the Google Form application. The data were analyzed through the stages of data reduction, data interpretation, and conclusion drawing. Finding: The results showed that 75% of teachers stated that they already had basic knowledge about online learning before the Covid-19 pandemic. 45.80% of teachers said they obtained information about online learning through school-facilitated training while 16.70% gathered information about online learning before the Covid-19 pandemic from government-facilitated training, and 37.50% obtained information about online learning from independent learning. A total of 54.10% of teachers stated had conducted online learning before the Covid-19 pandemic. However, only 20.80% of them stated that online learning is very effective to be implemented. Conclusion: The readiness of teachers to implement online teaching-learning depends on their knowledge and experience related to online learning. Inadequate teaching training causes the lack of understanding of teachers towards the benefits of supported information technology-based learning media.